Endothelial cells in tumor microenvironment: insights and perspectives - Leone, Patrizia; Malerba, Eleonora; Susca, Nicola; Favoino, Elvira; Perosa, Federico; Brunori, Giuliano; Prete, Marcella; Racanelli, Vito (Frontiers in Immunology, 2024)
The tumor microenvironment is a highly complex and dynamic mixture of cell types, including tumor, immune and endothelial cells (ECs), soluble factors (cytokines, chemokines, and growth factors), blood vessels and extracellular matrix. Within this complex network, ECs are not only relevant for controlling blood fluidity and permeability, and orchestrating tumor angiogenesis but also for regulating the antitumor immune response. Lining the luminal side of vessels, ECs check the passage of molecules into the tumor compartment, regulate cellular transmigration, and interact with both circulating pathogens and innate and adaptive immune cells. Thus, they represent a first-line defense system that participates in immune responses. Tumor-associated ECs are involved in T cell priming, activation, and proliferation by acting as semi-professional antigen presenting cells. Thus, targeting ECs may assist in improving antitumor immune cell functions. Moreover, tumor-associated ECs contribute to the development at the tumor site of tertiary lymphoid structures, which have recently been associated with enhanced response to immune checkpoint inhibitors (ICI). When compared to normal ECs, tumor-associated ECs are abnormal in terms of phenotype, genetic expression profile, and functions. They are characterized by high proliferative potential and the ability to activate immunosuppressive mechanisms that support tumor progression and metastatic dissemination. A complete phenotypic and functional characterization of tumor-associated ECs could be helpful to clarify their complex role within the tumor microenvironment and to identify EC specific drug targets to improve cancer therapy. The emerging therapeutic strategies based on the combination of anti-angiogenic treatments with immunotherapy strategies, including ICI, CAR T cells and bispecific antibodies aim to impact both ECs and immune cells to block angiogenesis and at the same time to increase recruitment and activation of effector cells within the tumor.